ARTICLE SENTENCE ANALYSIS: USE OF CLAUSES AND PHRASES IN SCIENTIFIC SENTENCES - CAWIR RUFINUS PURBA; YULIA ANGGRAINI; PUSPITA SARI; WANAPRI PANGARIBUAN; ISLI IRIANI INDIAH PANE (State University of Medan, 2023)
Sentence analysis in scientific articles is a literature study that can improve students' ability to think critically. Especially in articles that use English. Syntax analysis is the first step in reading writing before the reader can understand the meaning implied in an English sentence as a whole. This research is literature review research that aims to analyse sentence structure and determine the types of sentences, clauses, and phrases. By selecting the title of the article from the accredited journal Sinta, a search is carried out on each sentence and then classifying sentences and word combinations according to the character and type of sentences, clauses, and phrases.